2014
DOI: 10.3109/10715762.2014.899694
|View full text |Cite
|
Sign up to set email alerts
|

New insights into antioxidant strategies against paraquat toxicity

Abstract: Paraquat (PQ, 1,1'-dimethyl-4-4'-bipyridinium dichloride) is a highly toxic quaternary ammonium herbicide widely used in agriculture, it exerts its toxic effects mainly because of its redox cycle through the production of superoxide anions in organisms, leading to an imbalance in the redox state of the cell causing oxidative damage and finally cell death. The contribution of mitochondrial dysfunction including increased production of reactive oxygen species besides the reduction in oxygen consumption as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
145
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(151 citation statements)
references
References 79 publications
5
145
0
1
Order By: Relevance
“…The significant attenuation of alveolar collapse and collagen deposition in histological changes after RAPA treatment was comparable to the effects obtained previously with this model using other potential antifibrotic agents such as DHA and naringin (Chen J. et al, 2013;Chen Y. et al, 2013;Blanco-Ayala et al, 2014). Interestingly, the observation period of the test groups in our study (14 and 28 d after RAPA treatment) The blots with anti-TGF-β1 antibody and anti-α-SMA antibody are shown in (a) and (d), respectively, and densitometric analysis normalized against β-actin is shown in (b), (c), (e), and (f) differed from that of other studies of novel antifibrotic agents mentioned above.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The significant attenuation of alveolar collapse and collagen deposition in histological changes after RAPA treatment was comparable to the effects obtained previously with this model using other potential antifibrotic agents such as DHA and naringin (Chen J. et al, 2013;Chen Y. et al, 2013;Blanco-Ayala et al, 2014). Interestingly, the observation period of the test groups in our study (14 and 28 d after RAPA treatment) The blots with anti-TGF-β1 antibody and anti-α-SMA antibody are shown in (a) and (d), respectively, and densitometric analysis normalized against β-actin is shown in (b), (c), (e), and (f) differed from that of other studies of novel antifibrotic agents mentioned above.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have revealed that a combination of glucocorticoid and cyclophosphamide can improve the survival rate of PQ-poisoned patients or animal models, and reduce the pathological changes in the lung tissues, such as inflammatory cell infiltration, in the early stages of acute lung injury (ALI) (Rocco et al, 2003;Li et al, 2014), but this therapy does not have a significant effect in preventing progressive pulmonary fibrosis. Some other potential agents, such as docosahexaenoic acid (DHA) (Chen J. et al, 2013) and naringin (Chen Y. et al, 2013;Blanco-Ayala et al, 2014), have been shown to ameliorate PQ-induced pulmonary fibrosis in animal models. However, these new therapies take a relatively long time to achieve a noticeable antifibrotic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Severity at HEMS contact does not appear to be different between the medical agents group and the other agents group, but it seems that if a pesticide is associated as the cause, mortality increases well over the medical agents group. Paraquat, in particular, had a high case fatality rate, and 45.5% of fatal cases reported in two previous studies were caused by paraquat 5, 6. Seven paraquat poisoning cases were transported by the Kanagawa HEMS, and only two of those survived.…”
Section: Discussionmentioning
confidence: 89%
“…The usage of octreotide acetate and ornidazole sodium chloride in this patient is general usage when the patient appears to be intoxicated with paraquat and the amylase and lipase levels changes. Antioxidants are required to treat oxidative stress in paraquat poisoning (3)(4)(5) and paraquat-induced acute pancreatitis (6). Our patient, who had epilepsy and acute pancreatitis, was cured after receiving timely treatment.…”
Section: Discussionmentioning
confidence: 99%